Phylogenetic Group B2 Expressed Significant Biofilm Formation among Drug Resistant Uropathogenic Escherichia coli - Saima Javed (Taylor & Francis Group, 2021)
Biofilm is an important virulent marker attributed to the development of urinary tract infections (UTIs) by uropathogenic E. coli (UPEC). Drug-resistant and biofilm-producing UPEC are highly problematic causing catheter-associated or recurrent UTIs with significant morbidity and mortality. The aim of the current study was to investigate the prevalence of biofilm formation and phylogenetic groups in drug-resistant UPEC to predict their ability to cause disease. This prospective study was conducted at the Department of Microbiology, University of Karachi from January to June 2019. A total of 50 highly drug-resistant UPEC were selected for this study. UPEC isolates were screened to form biofilm by Congo-red agar (CRA) and microtiter plate (MTP) technique. The representative biofilm-producing isolates were analysed by scanning electron microscopy (SEM) monitoring. Phylogenetic analysis was done by PCR method based on two preserved genes; chuA, yjaA and TspE4-C2 DNA fragment. On CRA 34 (68%) UPEC were slime producers, while on MTP 20 (40%) were strong biofilm producers, 19 (38%) moderate and 11 (22%) were low to negligible biofilm producers. Molecular typing confirmed that phylogenetic group B2 was prevalent in drug resistant UPEC strains. Pathogenic strains belonged to phylogenetic group B2 and D were found to have greater biofilm forming ability as compare to non-pathogenic commensal strains that belonged to phylogenetic group A. Our results indicate that biofilm formation vary in drug resistant UPEC belonged to different phylogenetic groups. This study indicates possible link between in vitro biofilm formation and phylogenetic groups of UPEC, therefore this knowledge might be helpful to predict the pathogenic potential of UPEC and help design strategies for controlling UTIs.